Emergence of equine-like G3 and porcine-like G9 rotavirus strains in Sarawak, Malaysia : 2019−2021 - Ahmad Syatir, Tahar; Ong, Eng Joe; Andy, Rahardja; Dewi, Mamora; Lim, Khwang Thong; Kamruddin, Ahmed; Dorothy, Kulai; Tan, Cheng Siang (John Wiley and Sons, 2023)
Rotavirus is the leading causative viral agent of pediatric acute gastroenteritis globally, infecting mostly children 5 years old and below. Data on rotavirus prevalence in Malaysia is scarce, despite the WHO's recommendation for continuous rotavirus surveillance, and has underestimated the need for national rotavirus vaccination. Characteristics of the current rotavirus strains in Malaysia have to be determined to understand the rotavirus epidemiology and vaccine compatibility. This study sought to determine the genetic relatedness of Sarawak rotavirus strains with global strains and to determine the antigenic coverage and epitope compatibility of Rotarix and RotaTeq vaccines with the Sarawak rotavirus strains via in silico analysis. A total of 89 stool samples were collected from pediatric patients (<5 years old) with acute gastroenteritis at private hospitals in Kuching, Sarawak. Rotavirus was detected using reverse transcription-polymerase chain reaction. Positive amplicons were analyzed using nucleotide sequencing before phylogenetic analyses and assessment of epitope compatibility. Genotyping revealed G1P[8] (1/13; 7.7%), G3P[8] (3/13; 23%), G9P[4] (1/13; 7.7%), and G9P[8] (3/13; 23%), G9P[X] (1/13; 7.7%), GXP[4] (1/13; 7.7%), and GXP[8] (3/13; 23%) in samples. All wild-type Sarawak rotavirus strains, with the exception of G1, showed variations in their phylogenetic and antigenic epitope characteristics.